2022
DOI: 10.3390/machines10090804
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Tangential Contact Stiffness and Damping Model of the Solid–Liquid Interface

Abstract: In order to establish the tangential contact stiffness and damping model of the solid–liquid interface by tangential exciting vibration force under mixed lubrication, the finite difference method was firstly used to solve the average flow equation considering the effect of roughness on the lubrication effect, and the bearing capacity, shear force, and friction coefficient of the oil film were obtained, and thereby the dynamic tangential contact stiffness and damping of the oil film under tangential harmonic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Zhou et al [24][25] proposed a tangential stiffness and damping model by considering the coupling of gear stiffness and damping and oil film stiffness and damping. Peng et al [26] established a model of tangential stiffness and damping of solid-liquid interface when normal static load and tangential harmonic vibration occur, and thus verified it by experiments. Dwyer-Joyce et al [27] measured the normal contact stiffness of lubricating steel balls from static, mixed to full-film state when sliding on the steel disk by ultrasonic reflection method, and found that with the increase of sliding velocity, the contribution of liquid stiffness to the total stiffness gradually increased, and even became the main part, even in the static state, the liquid stiffness also contributed to the total stiffness.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Zhou et al [24][25] proposed a tangential stiffness and damping model by considering the coupling of gear stiffness and damping and oil film stiffness and damping. Peng et al [26] established a model of tangential stiffness and damping of solid-liquid interface when normal static load and tangential harmonic vibration occur, and thus verified it by experiments. Dwyer-Joyce et al [27] measured the normal contact stiffness of lubricating steel balls from static, mixed to full-film state when sliding on the steel disk by ultrasonic reflection method, and found that with the increase of sliding velocity, the contribution of liquid stiffness to the total stiffness gradually increased, and even became the main part, even in the static state, the liquid stiffness also contributed to the total stiffness.…”
Section: Introductionmentioning
confidence: 89%
“…From theoretical analysis and experimental demonstration in References [23,26,49], it can be seen that the total tangential contact stiffness of the relative motion solidliquid interface is the sum of the solid contact stiffness and the oil film tangential stiffness, and the total tangential damping is the sum of the solid contact damping and the oil film tangential damping. The tangential contact stiffness of solid-liquid interface is obtained from Equations ( 27) and ( 47).…”
Section: Calculation Model Of Tangential Contact Stiffness and Dampin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al 21 utilized a quadratic function to describe the profile of asperities and analyzed the influence of parameters such as lubrication medium, solid material, and asperity size on contact stiffness. Peng et al 22 developed a model for tangential contact stiffness and damping of the solid-liquid interface by considering tangential exciting vibration forces under mixed lubrication conditions. The dynamic tangential contact stiffness and damping of the solid-liquid interface were determined by summing the contributions from the solid surface contact and the solid-liquid contact in parallel under a microconvex Gaussian distribution.…”
Section: Introductionmentioning
confidence: 99%
“…utilized a quadratic function to describe the profile of asperities and analyzed the influence of parameters such as lubrication medium, solid material, and asperity size on contact stiffness. Peng et al 22 . developed a model for tangential contact stiffness and damping of the solid‐liquid interface by considering tangential exciting vibration forces under mixed lubrication conditions.…”
Section: Introductionmentioning
confidence: 99%